여자대학 인문 사회 예술계열 대학생의 취업 의식 및 교양교육 연구 ― C여자대학교를 중심으로 - 김은영; 이재성 (교양교육연구, 11(6), 2017)
본 연구의 목적은 여자대학교의 인문 사회 예술계열 대학생을 대상으로 취업의식과 취업 교육 현황을 조사 분석하여 취업관련 교과과정을 포함한 대학교육 교과과정을 제안하는 데 있다. 설문조사 결과, 여대생들은 4학년에 취업 준비를 시작하며(50.4%), 졸업 후 취업을 희망하고(73.6%), 전공 관련 취업(80.6%)을 원한다. 취업준비 정도는 학점, 외국어, 자격증 준비는 보통으로, 봉사활동, 해외경험, 해외인턴, 대외활동 준비는 ‘매우 적은’ 것으로 나타났다. 전공계열별로는, 인문계열은 학점과 외국어 준비를, 사회계열은 학점과 자격증 준비를, 예술계열은 공모전을 포함한 대외활동 준비가 두드러진다. 여대생들의 취업에 대한 태도를 살펴보면, 직장으로는 국가기관을, 직업으로는 문화/예술/디자인/방송을, 직무는 공무원을 선호하고 있다. 여대생들은 취업 교육을 위해 취업여건 조성(34.5%), 취업프로그램 개선(24.0%), 취업관련 교육과정 개선(21.3%)이 필요하다고 하였다. 여자대학들은 공통적으로 진로탐색, 직무이해, 현장실습(인턴십)을 운영하고 있으며, 취업 지원 프로그램을 탐색-직무-실전 등 단계적으로 제공하고 있다. 취업에 대한 여대생들의 요구를 바탕으로 시사점을 정리하면, 첫째, 조기 취업 준비, 둘째, 전공 교육과 취업 연계, 셋째, 취업 교육과정 체계화이다. 이러한 시사점을 통해 본 연구에서는 대학의 교육과정 중 교과 과정을 전공 교과과정, 교양 교과과정, 취업 교과과정으로 구성하여 대학의 기존 교육과정을 해치지 않으면서 학생들에게 다양한 교육의 선택권을 제공할 수 있는 안을 제안하였다. The purpose of this study is to propose a pathway to improve general education curriculum of women’s universities. To achieve this goal, this study examined and analyzed women university students’ perspectives on career paths, especially those whose majors are in the Humanities, Social Sciences, or Arts, as well as those universities’ current state of career development education. The findings indicate that women university students usually start their career preparation in their senior year(50.4%), hope to be employed after graduation(73.6%), and want to have a job related to their majors(80.6%). As part of an effort to prepare for future careers, women university students, on average, maintain a good GPA, learn a foreign language, and obtain a certificate. However, they rarely do volunteer work, experience overseas, work abroad as an intern, or participate in extracurricular activities. A breakdown of the findings by department is as follows: women university students in the Humanities maintain a good GPA and learn a foreign language, the students in the Social Sciences maintain a good GPA and obtain a certificate, and those in the Arts participate in extracurricular activities including art contests and exhibitions. As for women university students’ attitudes about future careers, they prefer government agencies as a workplace, Culture/Art/Design/Broadcasting as a vocation, and government employees as a job. Women university students reported that it is necessary to create career-oriented conditions for career education(34.5%), improve career guidance programs(24.0%), and amend career education curriculum(21.3%). All women’s universities provide programs for their students’ career exploration, understanding about work tasks, field placement(internship). The schools’ career support programs offer a step-by-step process of ‘exploration-work tasks-real-work experience’. The summary of the pathway for improvement that is based on women university students’ needs for future careers is as follow: having them to prepare for the early employment, making a link between majors and careers, and systemizing the career education curriculum. By developing universities’ curriculum with the majors, general education, and career education curriculum, this study proposed suggestions that could offer various educational options for students without deteriorating the existing education curriculum. KCI Citation Count: 5